Farmers Guidebook on Carp Production - Ali, Mohammad; Hossain, Md. Emdad; Nurun Nabi, S.M; Bhuyain, Mohammad; Shamsul, S.M. (WorldFish, 2022)
A comprehensive guideline for smallholder farmers on commercial carp fish farming and dyke cropping.